The CARE (Curiosity, Attentiveness, Respect and Responsiveness, and Embodiment) Model: Operationalizing Cultural Humility in the Conduct of Clinical Research - Sana Loue; Timothy Nicholas (Medicina, 2023)
Cultural competence training has been criticized for reinforcing existing stereotypes, ignoring intersectionality and inadvertently marginalizing some individuals and groups. In contrast, cultural humility offers the possibility of transformational learning, requiring individuals to pursue a lifelong course of self-examination. This approach makes authentic engagement with others possible. We review the premises underlying cultural competence and cultural humility, as well as proposed models for the integration of cultural humility into the clinical context. We propose a new model for the integration of cultural humility into clinical research: CARE, signifying Curiosity, Attentiveness, Respect and Responsiveness, and Embodiment. We conclude that the concept of cultural humility can be integrated into the conduct of clinical research.